Application of the 4Es in online crowdfunding platforms: A comparative perspective of Germany and China - Peter Konhäusner; Bing Shang; Dan Cristian Dabija (Journal of Risk and Financial Management, 2021)
As a dynamic way to raise funds for professional and private projects in recent years, crowdfunding has made tremendous progress, especially through online platforms. However, research on this subject is still young, leaving room for different perspectives. We therefore approach the marketing mix adaptability of online crowdfunding platforms and its impact on campaign efficiency and company strategy in two major economies: Germany and China. With the help of case examples based on secondary data, we performed an in-depth analysis of the 4E marketing mix benefits on crowdfunding, highlighting best practice approaches. We critically discuss the 4Es marketing mix approach, focusing on experience, value exchange, and marketing scales, and clarify the compatibility between crowdfunding and 4Es to better understand how these theories are applied to crowdfunding activities. As a result, the suitability of the 4E marketing mix adapted to crowdfunding needs is shown. From a market-oriented perspective, managers of crowdfunding platforms, as well as project owners from Germany and China, will be better able to attract their target audience by applying the 4E adaptation provided.
Keywords: 330; 4E; crowdfunding; fundraising; marketing mix; online crowdfunding platforms